(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The field of hospitality is the basis for the development of the economies of many countries of the world. Ukraine is no exception. Although the full-scale invasion of the territory of Ukraine left its mark on this sector of the economy, causing great damage to it, the global situation has not changed and its development remains one of the priorities, especially in the context of Ukraine’s vector for European integration. However, in today’s conditions, appropriate strategies and tools for their implementation are necessary to preserve and restore the competitiveness of the hospitality industry. The purpose of the article: to justify strategic alternatives for restoring the competitiveness of the hospitality sector of Ukraine Results. The article substantiates that since the field of hospitality is a complex socio-ecological-economic system, which is characterized by significant regional differences, it is advisable to apply combined strategic sets formed on the basis of a hierarchical approach. The application of three levels of strategic alternatives is substantiated: Level I as a market positioning strategy (globalization, deep market penetration, adaptation, anticipatory development); Level II as strategic directions for ensuring competitive advantages (creating new competitive advantages, increasing competitive advantages, maintaining a competitive position, restoring lost competitive advantages); Level III as typical competitive strategies (diversification, differentiation, focus, specialization, cost leadership). The results of the study were used to justify the correlation of the specified strategies with the identified trends in the development of the hospitality industry in the world and in Ukraine. The sets of alternative strategies will be identified in the coordinates "Level of competitive advantages" / "Level of competitiveness", according to which the regions of Ukraine will be grouped and the specifics of the implementation of each of the sets will be determined. In the conditions of the current situation, the proposals are characterized by a high level of speculation, but they can serve as a reference point for the development of the hospitality industry in the regions of Ukraine, the basis of regional programs and strategies, which is a perspective for further research. Conclusions. A strategic approach to restoring the competitiveness of the hospitality sector of Ukraine ensures the prediction and achievement of expected results, obtaining competitive advantages for the long-term perspective, is the basis for the development of regional strategies and programs, which is of practical importance.